Mendidik dengan Hati - Ahmad Sulthoni (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
Teachers should be the center controller of student education. The presence of teachers is not only to transmit knowledge and fill in the students’ brain. Their presence should be thorough as the figures giving affection to the students. Education can only be accomplished if teachers come with heart filled of knowledge and affection. Educating through heart means strategies and methods based upon teacher-self identification as the blossom figures having correct comprehension to their students. Their presence is not to be admired, to seek their mistakes or create fear but to give heart, knowledge, and affection. Educating through heart – at least, deals with the education process accomplished by comprehending the characteristics of student brains, giving attention, and revitalizing the student unique intelligence originating from observing efforts of students’ heart energy. Educating through heart can only be done by teachers having ‘’gold heart’’, or vice versa, through heart education strategy, teachers will have ‘’the gold heart’; the heart giving birth students having ‘’the gold heart’’ too.